Listening Strategies to Get the Main Ideas in Listening Comprehension Tasks - Sánchez Mercado, Lilieth del Carmen | Valle Mercado, Bryan Danilo | Sánchez Alvarado, Alber Sánchez Alvarado Alber (UNAN, Managua, 2021)
This research describes what kind of strategies students use to get the main idea in the listening task. Also, those strategies are cognitive, metacognitive and socio affective. The conceptual framework describes listening, listening comprehension, listening for main idea and the different types of listening strategies. Listening skill is considered to be one of the most difficult aspects for learners since they receive and interpret all the information in the communication process of a foreign language. On the other hand, the objective of this research is to identify the listening strategies that students from fourth year of the TEFL program, professionalization shift at UNAN-MANAGUA, use to find the main idea in listening texts.The participants were 10 students and 1 teacher, the data collection instruments consisted of a listening test for the students, the interview for the teacher, and the class observation guide for all the students and the teacher. According to the findings, students applied some cognitive strategies: note taking, underlining. In addition, metacognitive strategies that students used are: thinking aloud, making inference but those students also shown that they used comparing answer which is part of socio-affective strategies. Moreover, those strategies help students to grasp the main idea in the listening task